The Relation Between Endothelial Nitric Oxide Synthase Polymorphisms and Normal Tension Glaucoma. Issue 11 (November 2017) - Jeoung, Jin Wook; Kim, Dong Myung; Oh, Sohee; Lee, Jee-Soo; Park, Sung Sup; Kim, Ji Yeon
Abstract : Purpose: We investigated whether polymorphisms of the endothelial NO synthase ( eNOS ) gene are associated with normal tension glaucoma (NTG). We also investigated whether the eNOS polymorphisms are associated with NTG subgroups [NTG with and without optic disc hemorrhage (DH)]. Methods: A total of 251 patients with NTG and 245 healthy volunteers were enrolled in this study. DNA from peripheral blood leukocytes was extracted, and the genotypes of 4 polymorphisms (rs2070744, rs1549758, rs1799983, and rs2566514) in the eNOS gene were determined using restriction fragment length polymorphism and the SNaPshot method. The primary outcome was to investigate the relation between eNOS polymorphisms and NTG. The secondary outcome was to compare the frequencies of the polymorphic genotypes among the NTG subgroups. Bonferroni correction was used to adjust for type I error. Results: In all subjects, the genotype distribution was in accordance with Hardy-Weinberg equilibrium. None of the 4 polymorphisms showed any significant difference in the frequencies of alleles or genotypes between the NTG patients and controls. In the further analysis comparing the genotypic frequencies between NTG with DH and normal controls, the CC/CT genotype of rs2070744 was significantly associated with DH in NTG patients (genotypic association test, P -value=0.0041). On the multiple logistic regression analysis adjusted for covariates such as sex and age, the NTG with DH was associated with polymorphic genotypes of rs2070744 with a borderline significance (additive genetic model, P =0.0070). Conclusions: Our results indicates that eNOS rs2070744 can be associated with NTG patients with DH. This finding suggests that the eNOS polymorphism may be a genetic risk factor in the development of DH in NTG patients.